2020
DOI: 10.1136/bmjopen-2020-037159
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists’ pain attitudes and beliefs towards chronic low back pain and their association with treatment selection: a cross-sectional study

Abstract: ObjectivesThe main aim of this study was to investigate physiotherapists’ pain attitudes and beliefs towardss non-specific chronic low back pain (NSCLBP) and identify whether they are associated with treatment selection.DesignCross-sectional study.SettingSaudi Arabia (SA).ParticipantsAn online survey was distributed to physiotherapists from April 2018 to January 2019.Primary and secondary outcome measures(1) Biomedical and biopsychosocial treatment orientations were assessed using the Pain Attitudes and Belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
(45 reference statements)
2
15
1
Order By: Relevance
“…Study respondents' almost-universal endorsement of needling as an effective treatment for musculoskeletal disorders contrasts with lower rates of needling endorsement previously reported within the larger PT profession [30,32,35]. This disproportionately high enthusiasm for the practice is likely a reflection of the occupational subset of PTs surveyed, all of whom had elected to complete training in needling themselves.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Study respondents' almost-universal endorsement of needling as an effective treatment for musculoskeletal disorders contrasts with lower rates of needling endorsement previously reported within the larger PT profession [30,32,35]. This disproportionately high enthusiasm for the practice is likely a reflection of the occupational subset of PTs surveyed, all of whom had elected to complete training in needling themselves.…”
Section: Discussioncontrasting
confidence: 60%
“…A second Swedish study found that 56% of oncology-focused PTs treat patients using acupuncture (42% for cancer-related pain specifically) [31]. Fourteen percent of PTs studied in Saudi Arabia use acupuncture in clinical practice; and, usage was found to be more frequent among PTs with a stronger "biomedical" rather than "biopsychosocial treatment orientation" [32]. In the United Kingdom, 61% of surveyed PTs use acupuncture to treat contracted (frozen) shoulder [33]; and, at least a quarter use the technique to treat osteoarthritis of the hip [34].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various studies from different countries have demonstrated successful implementation of physical therapy at the first point of contact for patients with musculoskeletal conditions [21][22][23]. The biopsychosocial and biomedical orientations toward LBP appeared to be low among physiotherapists according to a recent study [24]. A stronger orientation toward biopsy-chosocial beliefs and attitudes regarding LBP management was associated with a better selection of guidelinebased physiotherapy interventions [24].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers suggested that factors such as the educational level of healthcare professionals, clinical experience, and number of patients treated may affect their treatment approach and choices (12)(13)(14)(15). In contrast, Alshehri et al (22), examining the relationship between the educational level of healthcare professionals and their CLBP-related attitudes and beliefs, concluded that educational level did not have an effect on the PABS-PT scores. Innes et al (23) determined that the number of patients treated had no effect on the chiropractors' biomedical or biopsychosocial beliefs and attitudes concerning CLBP.…”
Section: Discussionmentioning
confidence: 99%